Legal Design and ESG: contours and practical implications (Revista do Tribunal Regional Federal da 3ª Região, 2025)
Legal Design and ESG (Environmental, Social and Governance) are concepts that have gained notoriety in recent times in the legal field. With this in mind, and considering the new market direction based on sustainability and good corporate practices, in which organizations are invited to (re)think their business operations about the impacts of their activities, this paper aims to investigate the contours and practical implications of the integration between the Legal Design and ESG, based on a methodological approach based on deductive, exploratory research and centered on a bibliographic review. To this end, it will first present the concept of ESG, its interconnection with Law, and its developments and pillars, and then shed light on the Legal Design approach, especially regarding its resources and applications. In this way, it is possible to answer the following question: how can Legal Design contribute to the implementation of ESG in the corporate sphere? Given this panorama, it will be possible to establish a debate on the integration between Legal Design and ESG, both regarding the drafting of legal documents aimed at the organization's internal and external stakeholders, seeing how the Legal Design approach can contribute to the development and promotion of ESG.
Keywords: good corporate practices; sustainable development; ESG; Legal Design